Malignant lymphoma with a high content of epithelioid histiocytes. Issue 7 (July 1979) - Hayes, D; Robertson, J H
Abstract : A series of 12 patients with a rare malignant lymphoma containing numerous epithelioid histiocytes (MLEH), originally believed to be an atypical variant of Hodgkin's disease, is described. Clinicopathological studies suggest MLEH is a distinct entity among the non-Hodgkin's lymphomas which is generally resistant to therapy and has an unfavourable prognosis. Differentiation of the disease from angioimmunoblastic lymphadenopathy and Hodgkin's disease is discussed. In the necropsy case MLEH had transformed into a malignant lymphoma of histiocytic type.